“TUBIFEX INSTAN (FEXTAN)”: PAKAN ALTERNATIF BAGI UNIT PERBENIHAN IKAN LELE DI WILAYAH KABUPATEN NAGAN RAYA PROPINSI ACEH - Afrizal Hendri; Sufal Diansyah; Aris Yusdi; Sri Wahyuni; Mahyedin Salim; Burhanis Burhanis (Marine Kreatif, 2022)
One of the critical phases in the production of lele sangkuriang (catfish) seeds is the rearing of larvae - post larvae - seed. During this phase, its growth is strongly influenced by feed, in particular natural feed and or feed that suits the needs of the fish. Tubifex sp type natural feed is one type of feed that is generally used by Balai Benih Ikan,BBI, fish state hatchery) during the rearing period of lele sangkuriang seed. The results of discussions and sharing with technicians and employees of BBI Parom Nagan Raya and surrounding fish farmers, information was obtained that so far they have been very dependent on live tubifex type natural feed ordered from North Sumatera Province for lele sangkuriang rearing (for fourteen days of rearing). The need for live tubifex for one cycle of activity is 5 kg-10 kg, at a price of Rp.100.000/kg (IDR), excluding the cost of box packing + shipping costs to Nagan Raya. Departing from the problem of these partners (BBI), the implementation team of the Pengabdian Berbasis Riset (PBR) of Universitas Teuku Umar (UTU), has agreed to introduce science and technology in the form of introduction of instant tubifex/fexTan artificial feed. "Instant tubifex" is a type of artificial feed that is designed to resemble/ mimic which physically (color, shape) is like the original tubifex. It's just that this fexTan feed is easy to produce, raw materials in Aceh are very available, and the price per kg is still affordable/economically calculated and uses simple equipment. This PBR activity is carried out through two methods, namely lectures and discussions and demonstrations at partner locations. For information that this fexTan is produced from the main raw material for baby tuna (Thunnus sp) or known as sisik fish (local name), priced at Rp.50.000/kg and crude protein ±30%. Baby tuna fish that has undergone certain stages/processes, which are then molded based on the desired meshsize and put in plastic cups as packing containers and for subsequent use can be stored in the freezer. The results of PBR's activities for two days show that: i) there has been an increase in partner knowledge and competence about fexTan, ii) the availability of fexTan production facilities, iii) partner productivity has increased, iv) increased partner profits.